2021
DOI: 10.1530/eje-20-0636
|View full text |Cite
|
Sign up to set email alerts
|

DNAJC3 deficiency induces β-cell mitochondrial apoptosis and causes syndromic young-onset diabetes

Abstract: Objective: DNAJC3, also known as P58IPK, is an Hsp40 family member that interacts with and inhibits PKR-like ER-localized eIF2α kinase (PERK). Dnajc3 deficiency in mice causes pancreatic β-cell loss and diabetes. Loss-of-function mutations in DNAJC3 cause early-onset diabetes and multisystemic neurodegeneration. The aim of our study was to investigate the genetic cause of early-onset syndromic diabetes in two unrelated patients, and elucidate the mechanisms of β-cell failure in this syndrome. Methods: Whole e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 52 publications
5
57
0
1
Order By: Relevance
“…Although DNAJC3 has been widely acknowledged in the attenuation of proteins involved in the initial ER response (Schorr et al, 2015), changes in ER morphology or increased ER calcium leakage were not described previously in the context of the underlying pathophysiology (Synofzik et al, 2014). However, an increased sensitivity against additional ER stress burden was identified in DNAJC3-silenced rat and human β cells (Lytrivi et al, 2021). In accordance with these previous observations, our findings suggest only a minor UPR-activation mirrored by the altered abundance of ER-stress-related proteins (Figure 3).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Although DNAJC3 has been widely acknowledged in the attenuation of proteins involved in the initial ER response (Schorr et al, 2015), changes in ER morphology or increased ER calcium leakage were not described previously in the context of the underlying pathophysiology (Synofzik et al, 2014). However, an increased sensitivity against additional ER stress burden was identified in DNAJC3-silenced rat and human β cells (Lytrivi et al, 2021). In accordance with these previous observations, our findings suggest only a minor UPR-activation mirrored by the altered abundance of ER-stress-related proteins (Figure 3).…”
Section: Discussionmentioning
confidence: 91%
“…GGA1, ADP-ribosylation factor-binding protein GGA1; SMARCB1, SWI/SNF-related matrix-associated actin-dependent regulator of chromatin subfamily B member 1; SDHB, succinate dehydrogenase; SOAT1, Sterol O-acyltransferase 1; CHMP6, charged multivesicular body protein 6; ACADSB, short/branched chain specific acyl-CoA dehydrogenase; ETHE1, persulfide dioxygenase ETHE1; SERPINE2, Glia-derived nexin; PLPP1, phospholipid phosphatase 1; PLIN2, perilipin-2; PTRH2, peptidyl-tRNA hydrolase 2; AARS, alanine-tRNA ligase, cytoplasmic; ALAD, delta-aminolevulinic acid dehydratase; SYNPO2, synaptopodin-2; OCIAD2, OCIA domain-containing protein 2; SF3B4, splicing factor 3B subunit 4; HTATSF1, HIV tat-specific factor 1; APOOL, MICOS complex subunit MIC27; ADD3, gamma-adducin; DNAJC3, DnaJ homolog subfamily C member 3. the secretory machinery, DNAJC3 mutant fibroblasts exhibit ER dysfunction (Synofzik et al, 2014). An increased sensitivity against additional ER stress burden was identified in DNAJC3silenced rat and human β cells (Lytrivi et al, 2021). Notably, several publications demonstrated that cellular cholesterol accumulation leads to UPR activation (Feng et al, 2003;Cunha et al, 2008;Fu et al, 2011).…”
Section: The Endoplasmic Reticulum Is More Vulnerable Against Stress In Dnajc3 Mut Fibroblastsmentioning
confidence: 99%
See 2 more Smart Citations
“…This gene has been mainly implicated in the development of diabetes [ 37 , 38 ], but also neurodegeneration [ 37 ]. The pathomechanism of diabetes caused by DNAJC3 mutations further involves mitochondrial degeneration [ 39 ]. Thus, it could be also speculated that this gene might be functionally linked to the development of BCSE in cattle.…”
Section: Discussionmentioning
confidence: 99%